2014
DOI: 10.1073/pnas.1321605111
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity when young provides lifelong benefits to cortical bone size and strength in men

Abstract: The skeleton shows greatest plasticity to physical activity-related mechanical loads during youth but is more at risk for failure during aging. Do the skeletal benefits of physical activity during youth persist with aging? To address this question, we used a uniquely controlled cross-sectional study design in which we compared the throwing-to-nonthrowing arm differences in humeral diaphysis bone properties in professional baseball players at different stages of their careers (n = 103) with dominant-to-nondomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(171 citation statements)
references
References 39 publications
6
157
1
1
Order By: Relevance
“…Studies of age-related changes in trabecular density or cortical bone relative thickness in Iron/Roman through early industrial European samples have produced mixed results, with some reporting less decline than in modern populations (64)(65)(66) and others finding no difference or even more negative trends in the earlier samples (67)(68)(69). The results of the present study suggest that only very vigorous exercise is a sufficient stimulus for increasing bone strength, as a possible protective mechanism for age-related bone loss (21,22).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Studies of age-related changes in trabecular density or cortical bone relative thickness in Iron/Roman through early industrial European samples have produced mixed results, with some reporting less decline than in modern populations (64)(65)(66) and others finding no difference or even more negative trends in the earlier samples (67)(68)(69). The results of the present study suggest that only very vigorous exercise is a sufficient stimulus for increasing bone strength, as a possible protective mechanism for age-related bone loss (21,22).…”
Section: Discussioncontrasting
confidence: 49%
“…Although skeletal morphology is determined by a complex interplay between various genetic and environmental factors (18,19), there is abundant evidence that mechanical loading during life has a strong influence on skeletal structure (20)(21)(22)(23). Earlier studies identified declines in skeletal robusticity (strength relative to body size) in Homo throughout the Pleistocene (24,25), but recent analyses suggest that the major decrease in robusticity occurred later, at the end of the Pleistocene, between early anatomically modern H. sapiens and Holocene populations (26,27).…”
mentioning
confidence: 99%
“…A well-known example of focal adaptation to physical demand is the humeral hypertrophy of the playing arms of tennis players and baseball pitchers relative to their non-playing arms (Jones et al, 1977;Haapasalo et al, 2000;Warden et al, 2014). Implicitly, these athletes demonstrate the ability of bone to perceive and respond to biophysical signals in a sitespecific manner, perhaps to maintain an optimal mechanical environment to cells regulating the response (Rubin, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…1 [8]. Similarly, the throwing arm of baseball players has been shown to have increased bone mass and improved structure as compared with the non-throwing arm [9]. Running [10][11][12], jumping [13], gymnastics [14,15], weight lifting [16], and swimming [17,18] have all been shown to increase bone mass as compared to sedentary controls.…”
Section: Figmentioning
confidence: 98%